Comparative efficacy and safety of preventive treatment with cytovir-3 and arbidol in children during seasonal outbreak of respiratory viral infection (an open-label randomized clinical study) - V. S. Smirnov (Sankt-Peterburg : NIIÈM imeni Pastera, 2019)
Aim: To compare the safety and prophylactic efficacy of Cytovir-3 and Arbidol in an open-label randomized clinical trial in children at seasonal risk of infectious respiratory disease.Methods: This study was performed in the period preceding a seasonal outbreak of acute respiratory viral infections (ARVI) and influenza. The study enrolled apparently healthy children aged 6 to 18 years without contra-indications to either Cytovir-3 or Arbidol. Cytovir-3 was given as 1 capsule per day, each day in a fasted state for 12 days. Arbidol was taken as a 100 mg capsule twice a week for three weeks. Following dosing, subjects were followed-up for a further three weeks. Overall health and presence of symptoms of either ARVI or influenza were monitored daily in all subjects. The level of sIgA in saliva was baselined before treatment and measured at the end of the follow-up period.Results: Most subjects did not exhibit any change in overall health status during the dosing and follow-up periods. The first two cases of illness in subjects receiving Cytovir-3 were diagnosed at the end of the third week after completion of dosing. In those subjects receiving Arbidol the first cases of illness were reported at the end of the second week following the end of prophylactic dosing. All patients displayed a significant increase in sIgA level at the end of the dosing period, but this was more pronounced in the Cytovir-3 group. Conclusion: The results of this comparative randomized clinical trial confirmed the safety and tolerability of both medications, and that the prophylactic efficacy of Cytovir-3 is equal to that of Arbidol.